OBJECTIVELY MEASURED SLEEP AND DECLINE IN PERFORMANCE-BASED PHYSICAL FUNCTION IN OLDER MEN. (11th November 2018) - Holingue, C; T Owusu, J; Tzuang, M; Yaffe, K; Stone, K L; W Rebok, G; Ancoli-Israel, S; P Spira, A
Abstract: Little is known about links between objectively measured sleep and decline in physical performance among older adults. We investigated the association of actigraphically-measured total sleep time (TST), wake after sleep onset (WASO), and sleep efficiency (percent time in bed spent asleep) with substantial (highest decile) decline in objective measures of physical performance 3.4 ± 0.6 years later among 2, 441 men (age=75.7 ± 5.2). In adjusted analyses, compared to men in the middle TST tertile (mean=6.5 ± 0.3 hours), those in the shortest-sleeping tertile (mean=5.1 ± 0.9 hours) had greater odds of decline in grip strength (odds ratio (OR)=1.12), gait speed (OR=1.55), best narrow-walk time (OR=1.50), and chair-stand speed (OR=1.55); men in the longest-sleeping tertile (mean =7.6 ± 0.6 hours) had greater odds of chair-stand decline (OR=1.51), all p<0.05. Neither WASO nor sleep efficiency was associated with our outcomes. Older men with shorter or longer sleep duration have a greater risk of physical performance decline.